Motivation-Driven Knowledge Transfer in Higher Academic Institutions in Nepal - Rai, Rahan Singh (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
This study aims to explore the factors affecting the transfer of knowledge in Higher Academic Institutions (HAIs), with particular emphasis on the role of intrinsic (autonomous) and extrinsic (controlled) motivation. A descriptive along with quantitative research design was adopted for this investigation. A purposive sampling method was emloyed to select respondents who were directly involved in academic and knowledge transfer activities. A total of 415 questionnaires, measured on seven-point Likert type scales, were distributed among faculty members. Of these, 395 valid responses were retained for further statistical analysis. Both descriptive and inferential measures were performed to analyze the collected data. Descriptive statistics were used to summarize demographic features and key study variables. The consistency of the items was measured using Cronbach’s alpha. The relationships between transfer of knowledge and both independent variables were assessed using correlation analysis, while regression of multiiple predictors was carried out to test the proposed hypotheses. The outcomes reveal that both intrinsic (autonomous) motivation and extrinsic (controlled) motivation exert a statistically significant and positive impact on transfer of knowledge.The study makes an important theoretical and practical contribution by providing empirical evidence on the motivational determinants of knowledge transfer within HAIs. It can support internal policy development and the effective utilization of institutional resources to boost up knowledge transfer practices in higher acadmic institutions in Nepal.